PENGARUH PENGETAHUAN PEMASARAN TERHADAP HUBUNGAN DENGAN PELANGGAN MELALUI KUALITAS KOMUNIKASI DAN ADAPTABILITAS - Suliyanto . (Jurnal Bisnis dan Ekonomi, 2013)
Puposes of this study were to explain the influence of marketing knowledge on communication quality and marketing adaptabilitation olso to analysis influence of communication quality and marketing adaptabilitation on customer relationship.To test the empirical models, Structural Equation Modeling (SEM) was used. Sample size of this research were 200 owners and/or managers of Small and Medium Enterprises (SMEs) running food and beverage sector in the residency Banyumas areas. The results showed that marketing knowledge has a positive effect on communication quality and marketing adaptabilitation, marketing quality has a positive effect on customer relationship, but marketing adaptabilitation has no positive effect on customer relationship. Key words: Marketing knowledge, communication quality, marketing adaptabilitation, customer relationship.